Fast or slow: applying life history strategies to responsible gambling adherence. Issue 3 (2nd September 2022) - He, Mu; Chen, Juliet Honglei; Wu, Anise M. S.; Tong, Kwok Kit
ABSTRACT: From the evolutionary perspective, life history (LH) strategies have been used to account for individual differences in behaviors and traits such as impulsivity, sensation seeking, and risk-taking propensity. The present study aimed to extend the application of LH strategies based on the psychometric approach to study individual differences in endorsing protective gambling beliefs and adopting responsible gambling (RG) behaviors. We conducted a telephone survey in Macao, China, and acquired a community-dwelling Chinese adult sample ( N  = 697) with the two-stage cluster random sampling method. Regression analyses showed that individuals with slower LH strategies displayed higher levels of protective gambling beliefs and RG behaviors. As hypothesized, protective gambling beliefs demonstrated a positive association with RG behaviors; furthermore, we found its partial mediating effect on the relationship between LH strategies and RG behaviors. Our findings suggested that one could take LH strategies into account in understanding individual differences in adopting RG behaviors and designing tailored measures to promote RG adherence. The present study also highlighted the effect of protective gambling beliefs in exploring the underlying mechanism of the link between LH strategies and RG behaviors, pointing to a potential avenue in fostering protective gambling beliefs to further increase RG adherence.